Simultaneous spectrofluorometric analysis of tablets containing hydrochlorothiazide combined with timolol maleate or amiloride hydrochloride - Wedian Fadel; Lataifeh Anas; Mohammed Makaseb S. (Acta Pharmaceutica)
Green and sensitive spectrofluorometric methods have been developed and validated for the determination of timolol maleate (TML)/hydrochlorothiazide (HCT) and amiloride hydrochloride (AMH)/hydrochlorothiazide in tablets. The proposed spectrofluorometric procedures were found to be linear in the range of 4–12, 5–35 and 0.025–0.2 mg L−1 for HCT, TML and AMH, resp. The excitation and emission wavelengths for HCT, TML and AMH at room temperature were 270 and 375, 295 and 435, 330 and 415 nm, resp. The methods were validated with respect to ICH guidelines. The AMH showed higher sensitivity with lower values of LOD and LOQ values compared to HCT and TML. The proposed methods were applied to two pharmaceutical formulations; the method for HCT and AMH has proven as reliable assaying method, whereas the method for TML, when combined with HCT, is applicable to screening semi-quantitative analyses.